1988
DOI: 10.1021/np50059a012
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Staurosporine, 1. 1H- and 13C-nmr Assignments

Abstract: Complete and unambiguous assignments of the 1H- and 13C-nmr spectra of the potent antitumor antibiotic staurosporine have been accomplished using a combination of one- and two-dimensional nmr techniques, including one-bond and long-range heteronuclear multiple-quantum coherence spectroscopy (HMQC). Staurosporine was found to be highly cytotoxic in the KB and P-388 assays but was inactive in the microtubulin assembly assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…The identity of the predominant ICZ compound, STA, produced by strain FMA was confirmed by MS and 1 H NMR analysis, which were identical to those previously reported [30] (Figure S4 and Figure S5, Supplementary Materials). The two compounds produced by spcI mutant were isolated, and their structures were determined by MS, 1 H NMR, 13 C NMR, 1 H– 1 H COSY, HSQC and HMBC (for two) data (Figure S6, Figure S7, Figure S8, Figure S9, Figure S10, Figure S11, Figure S12, Figure S13, Figure S14, Supplementary Materials).…”
Section: Resultssupporting
confidence: 84%
“…The identity of the predominant ICZ compound, STA, produced by strain FMA was confirmed by MS and 1 H NMR analysis, which were identical to those previously reported [30] (Figure S4 and Figure S5, Supplementary Materials). The two compounds produced by spcI mutant were isolated, and their structures were determined by MS, 1 H NMR, 13 C NMR, 1 H– 1 H COSY, HSQC and HMBC (for two) data (Figure S6, Figure S7, Figure S8, Figure S9, Figure S10, Figure S11, Figure S12, Figure S13, Figure S14, Supplementary Materials).…”
Section: Resultssupporting
confidence: 84%
“…Each of the protons in 1 and 2 were assigned using a combination of chemical shift data and coupling constants from the 1 H NMR spectrum (Table 1) and correlations from a COSY spectrum (Figure 2). Analysis of the chemical shift and coupling constant data indicated that the glycosidic unit matched that in staurosporine [22,23,24,25]. An HSQC experiment enabled the assignments of each methine, methylene and methyl carbon (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent HMBC data facilitated the assignment of the remaining carbons (Table 1) with the exception of C-4c, C-5, C-7 and C-7a, which were interpreted by comparison with the literature [22,23,24,25]. Further long range correlations observed in the HMBC spectrum (Figure 2) provided definitive proof for the connectivity and thereby confirmed the structural assignment of 1 and 2 as 2-hydroxy-7-oxostaurosporine and 3-hydroxy-7-oxostaurosporine, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 198a was isolated as white powder from fraction V using column chromatography on silica gel, followed by PTLC and finally purified on Sephadex Only one compound with this formula has been obtained from microorganisms so far: staurosporine (198a) [303] . This assumption was confirmed indeed by the from Streptomyces staurosporeus Awaya (AM-2282) [304] and subsequently from several other actinomycetes.…”
Section: Staurosporinementioning
confidence: 99%